2018
DOI: 10.35726/jp.v23i1.291
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Total Plate Count (Tpc) Pada Daging Sapi Yang Diambil Di Rumah Potong Hewan (Rph) Kota Kupang

Abstract: The Increasing of beef consumption in Kupang City, shows that there is an increase in people's need for animal protein. However, high meat consumption can also be a threat to health if contaminated by microorganisms.This study aims to calculate the amount of microbial contamination in beef samples taken from Kupang City Slaughterhouse. 30 longissimus dorsi muscle samples were taken from RPH and taken to the Kupang City Veterinary Engineering Unit to be examined using the Total Plate Caount Test (TPC), then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Yunanda et al (2020) stated that the shelf life of meat would be shorter as the total plate count increases. Added by Jacob et al (2015), physically and chemically, the meat would change rapidly. There were changes in color, consistency, and foul odor.…”
Section: Resultsmentioning
confidence: 99%
“…Yunanda et al (2020) stated that the shelf life of meat would be shorter as the total plate count increases. Added by Jacob et al (2015), physically and chemically, the meat would change rapidly. There were changes in color, consistency, and foul odor.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 100% of the meat samples exhibited TPC values that met the SNI standards. In contrast, Jacob et al [19] showed that 63.33% of the meat samples failed to meet the SNI standards in Kupang, while Mufidah et al [20] attained a value of 33.33% for the same in Probolinggo, East Java. The different levels of microbial contamination are influenced by differences in the hygiene and sanitation applications in each slaughterhouse.…”
Section: Microbial Contamination Levelsmentioning
confidence: 96%
“…Daging yang jumlah mikroba banyak akan lebih cepat mengalami proses pembusukan (Hernando et al, 2015). Hasil analisis mikrobiologi Total Plate Count (TPC) daging sapi yang diambil di RPH Kota Kupang dan RPH Kota Pekanbaru berada di atas standar normal (Kuntoro et al, 2013;Jacob et al, 2018).…”
Section: Pendahuluanunclassified
“…Selain peralatan dan cara penanganan, kontaminasi juga dapat terjadi melalui lantai tempat pemotongan. Daging yang diletakkan di lantai setelah penyembelihan juga dapat terkontaminasi dengan mikroba yang ada di lingkungan lantai (Rananda, 2016;Jacob et al, 2018). Ditambahkan oleh Kuntoro (2013) dan Gaznur (2017), faktor pengepakan, pengiriman dan penyimpanan serta pengolahan daging sebelum dikonsumsi dapat menjadi faktor lain terjadinya kontaminasi mikroba pada daging.…”
Section: Cemaran Mikrobaunclassified